Learner autonomy in the light of Freire Autonomia do aprendiz à luz de Freire - Christine Siqueira Nicolaides; Vera Fernandes (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2008)
Concepts on autonomy in language learning usually converge to the responsibility over one's own learning. This paper aims to emphasize that learner autonomy is also a matter of getting involved with the social environment in which the learner is inserted in. This conception will be analyzed in the light of Freire's Critical Pedagogy. OTÁVIO, considered a "rebel" by his own teachers, is brought up as a case study to illustrate kinds of transformation, which might happen under the influence of the environment and of the opportunities generated in it. Concepções sobre autonomia do aprendiz geralmente convergem para a responsabilidade sobre seu aprendizado. Este artigo tem por objetivo enfatizar o fato de que autonomia do aprendiz é também uma questão de envolver-se com o ambiente social no qual está inserido. Essa concepção será analisada sob a luz da Pedagogia Crítica de Freire. OTÁVIO, considerado um "rebelde" por seus próprios professores, é trazido à tona como um estudo de caso para ilustrar tipos de transformações que podem acontecer influenciadas pelo meio e pelas oportunidades nele geradas.